Ecosystem services : global issues, local practices - Jacobs, Sander; Dendoncker, Nicolas; Keune, Hans. (Amsterdam ; Boston : Elsevier, 2014)
Ecosystem Services: Global Issues, Local Practices is a hands-on, transdisciplinary reflection on ecosystem services directed toward the future development of research, practice, and implementation by professionals. The diversity of values assigned to ecosystems and their services are used to inform policy from local to global scales."--Publisher description.
boek